2017
DOI: 10.17744/mehc.39.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Counselors' Attributions of Blame Toward Female Survivors of Battering

Abstract: Intimate partner violence (IPV) is a social problem that affects roughly 5.3 million women in the U.S. each year, accounts for 1,300 deaths, and often results in a number of physical and mental health consequences. Many women seek counseling as a way to find relief from the symptoms of the abuse they have endured.Unfortunately, women often find the available resources to be inadequate or worse, damaging. Misdiagnosis, non-violent re-victimization, and even blame are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 142 publications
(364 reference statements)
0
3
0
Order By: Relevance
“…Problematic biases related to IPV are largel attributable to a poor understanding of the complex dynamics contributing to IPV (Perrin, 2017; Tarzia et al, 2021). IPV is marked by a chronic pattern of coercive control functioning to maintain one partner’s power over the other (Notestine et al, 2017). Questioning why a victim stays with an abuser, for example, implies that he or she could choose to leave the abusive relationship (Perrin, 2017).…”
Section: Problematic Bias and Dynamics Of Ipvmentioning
confidence: 99%
“…Problematic biases related to IPV are largel attributable to a poor understanding of the complex dynamics contributing to IPV (Perrin, 2017; Tarzia et al, 2021). IPV is marked by a chronic pattern of coercive control functioning to maintain one partner’s power over the other (Notestine et al, 2017). Questioning why a victim stays with an abuser, for example, implies that he or she could choose to leave the abusive relationship (Perrin, 2017).…”
Section: Problematic Bias and Dynamics Of Ipvmentioning
confidence: 99%
“…More traditional beliefs about gender and sexist attitudes also have been associated with victim blaming for both sexual and non-sexual forms of IPV (Erickson et al, 2017;Koepke et al, 2014;Penone & Spaccatini, 2019;Stewart et al, 2012). This relationship, between sexist attitudes and victim-blaming for IPV, has even been demonstrated among mental health counselors (Notestine et al, 2017).…”
Section: Observer Characteristicsmentioning
confidence: 97%
“…Yamawaki et al ( 2009 ) found that individuals higher in benevolent sexism had greater tendencies to blame victims of rape, and Notestine et al ( 2017 ) found that ambivalent sexism was a significant predictor of blaming battered females. This may be because people who endorse benevolent sexism see women in need of protection when their actions align with stereotypical gender roles.…”
Section: Introductionmentioning
confidence: 99%